From Scroll to Soul: How Social Media Builds Travel Brands - Sharma, Dilli Raj; Shah, Binod; Mahato, Bijay (The Gaze: Journal of Tourism and Hospitality, 2024)
This study aims to examine the impact of social media networks' interactivity, benefits, and incentives on the brand image of Nepal's tourism industry. This study used a quantitative research design to gather data through a standardized questionnaire. This questionnaire was distributed among a carefully selected sample of 384 respondents, each chosen based on their potential to provide relevant and specific insights related to the research objectives. Correlation and regression methodologies were utilized to investigate the connections between the variables. The findings show the interactivity of social media, the benefits of social media, and the incentives of social media all substantially impact the image of a company in the Nepalese setting. These findings highlight the critical role that social media engagement initiatives play in changing perceptions of brands in the tourism industry. By providing empirical evidence on the impact of social media components on brand image, the study contributes to the current body of literature. It also offers significant insights for tourist marketers and stakeholders looking to promote brand equity using digital platforms.